Social Media Utilization in Food Businesses in the 2nd District of Albay - Amador, Radge (JPAIR Multidisciplinary Research, 2025)
The study investigates the utilization of social media by food businesses in the 2nd District of Albay, focusing on its advantages and disadvantages. With the rapid growth of digital platforms, understanding the impact of social media on business operations is crucial for fostering economic success. The primary aims of this research were to assess the current status of food businesses regarding social media usage, identify the benefits and challenges they encounter, and provide actionable recommendations for enhancing their social media strategies. To achieve these aims, a descriptive quantitative research design was employed, utilizing a self-administered survey questionnaire distributed to 50 food establishments in Daraga and Legazpi. Analysis included frequency counting and the calculation of weighted means to evaluate responses. Findings revealed that while businesses recognize the benefits of social media for customer engagement and marketing, they also face significant challenges, such as time constraints and managing negative reviews. The study concludes that effective social media management requires investment in training and strategic planning. By addressing these challenges and leveraging the advantages offered by social media, food businesses can enhance their operations, improve customer relations, and ultimately achieve greater economic success.
Keywords: Business and Management; social media; food businesses; customer engagement; marketing strategies; digital marketing; social media challenges; descriptive quantitative design; Albay; Philippines